Analisis Pertumbuhan Tanaman Tembakau (Nicotiana tabacum L.) pada Media Tanam yang Diperkaya Azotobacter dan Biohumic - Sri Nur Qadri; Abd. Rahim; Nirmala (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2026)
The long-term dependence of tobacco farmers on synthetic chemical fertilizers may reduce soil quality and crop productivity. One of the main challenges in tobacco production is producing high-quality seedlings that can support optimal plant productivity. This study aimed to determine the best bioagent treatment to tobacco. The used a non-factorial randomized block design with four growing-media treatments: P0 (control), P1 (Azotobacter), P2 (Biohumic), and P3 (Azotobacter + Biohumic). Each treatment was replicated three times. The results showed that the combination of Azotobacter and Biohumic (P3) produced the highest mean values for all observed plant growth parameters. This response was presumably associated with the synergy between nitrogen fixation by Azotobacter and improved nutrient availability and root-zone conditions by Biohumic.